Analisis Model Pengaturan Relay Arus Lebih dan Relay Gangguan Tanah Saluran Tegangan Tinggi di Gi Miwon Ke PT Daesang - Abdul Muta’ali; Hifdillah Kharisma Muhammad (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Power system protection plays a crucial role in maintaining the reliability and security of electricity distribution. This study discusses the analysis of coordination between overcurrent relays (OCR) and ground fault relays (GFR) on the Miwon Substation power line. The study aims to determine the optimal setting values ​​for OCR and GFR, so that they can detect and disconnect short circuit faults quickly and accurately. The approach used includes theoretical calculations and simulations to evaluate relay performance under various fault conditions. The results of the study reveal that with appropriate settings, the relay can operate selectively and efficiently, reducing the impact of disturbances and maintaining the stability of the power system.